Rapid CD4 decline prior to antiretroviral therapy predicts subsequent failure to reconstitute despite HIV viral suppression - Majid Darraj; Leigh A. Shafer; Shanna Chan; Ken Kasper; Yoav Keynan (Elsevier, 2018)
HIV-1 infection is characterized by loss of CD4 T cells, leading to immunodeficiency. Initiation of antiretroviral therapy (ART) results in suppression of the viral load and increased CD4 counts. Both viral and host factors determine CD4 cell responses to ART with approximately 15-30% of individuals having suboptimal increase of CD4 T cell count, most commonly due to lack of compliance to ART. A smaller fraction of patients will have immune reconstitution failure and suboptimal CD4 increase despite suppression of HIV replication, and these individuals are at risk for adverse health outcomes. We sought to characterize the factors associated with decreased immunological response among Manitoba's HIV patient population.This retrospective case-control study included HIV patients with immune reconstitution failure despite suppression of HIV replication by ART. The immune reconstitution failure was defined by CD4 cell count increase from baseline of less than 100 CD4 cells/mm3 or lack of increase to above 200 CD4 cells/mm3 within one year of viral load suppression. Age and nadir CD4 cell counts are known risk factors associated with immune reconstitution failure. We chose controls (Patients with immune reconstitution success) of similar age and CD4 nadir cell with cases (Patients with immune reconstitution failure). We explored the potential effects of gender, HLA type, presence of co-infection, ethnicity, ART type, and rate of pre-treatment CD4 decline among cases and controls. Of more than 550 patients followed by our HIV clinic, 42 individuals met our definition of immune reconstitution failure and they were assigned to the cases group. 31 patients, comprising a range of ages and CD4 nadirs similar to those of the cases, were assigned to the control group. Our primary analysis was a regression model, predicting post-ART change in CD4 over time.After controlling for age and nadir CD4 cell counts, the only potential predictor that appears consistently associated with the rate of post-ART rise in CD4 over time in our cohort, regardless of the other variables that we have controlled for, is the rate of decline in CD4 pre-ART initiation.Several factors have been variably correlated with immune reconstitution failure of CD4 T cell count. Age and low CD4 nadir are factors previously shown to correlate with immune reconstitution failure; and we have controlled for them in our study. Another possible predictor is the rate of decline in CD4 pre-ART, which can serve as an additional marker of reconstitution failure and necessitate prioritizing individuals to ART initiation or identification of a subset of individuals that may be targeted for future adjunct strategies to improve immune recovery. Keywords: HIV, CD4, Immune reconstitution, Virologic suppression